Improving Tourism Package Configuration in Web Environment - Fuerstner, Igor; Nadj, Atila (International Journal of Industrial Engineering and Management, 2012)
The customers can use numerous specialized services that are available on the Internet, if they want to configure a tourism package. These services can be of lesser or greater complexity but most of them configure an offer from a series of picking lists from which a customer should pick an option. This can often be rather time-demanding and frustrating, especially when the customer has no real knowledge about the offered options. Therefore, this paper proposes the structure of a web-based tourism package offer, which enables the configuration of a tourism package for a specific destinationin a time-effective way, accompanied with a case study. Article history: Received (10 November 2012); Revised (28 November 2012); Accepted (08 December 2012)